An investigation of the relationship between Western Australian nickel laterites’ leaching performance and their mineralogical properties - Wang, Xiaodong (Curtin University, 2013)
Reasons for the variable acid leaching performance of the nickel laterite ore samples from Western Australia were investigated using numerous microstructural analytical techniques. Cementation of goethite-silica/silicate was identified as the main factor inhibiting acid leaching. Another major outcome of the research was significant improvement of quantitative phase analysis of turbostratically disordered nontronite by developing phase models with peak shape descriptions in X-ray diffraction analysis.